169 Prognostic Factors for Survival in Surgical Series of Symptomatic Metastatic Epidural Spinal Cord Compression: A Prospective North American Multicenter Study in 145 Patients. (August 2015) - Nater-Goulet, Anick; Fehlings, Michael G.; Tetreault, Lindsay; Kopjar, Branko; Arnold, Paul M.; Dekutoski, Mark B.; Finkelstein, Joel; Fisher, Charles; France, John; Gokaslan, Ziya L.; Rhines, Laurence D.; Rose, Peter; et al.
Abstract : INTRODUCTION: Symptomatic Metastatic Epidural Spinal Cord Compression (MESCC) afflicts up to 10% of all cancer patients and is associated with shortened survival and worsened quality of life. This study aims to identify the key survival prognostic factors in MESCC patients who were surgically treated for a single symptomatic lesion. METHODS: One hundred forty-two MESCC patients were enrolled in a prospective North American multicenter study and followed postoperatively for 12 months. With the use of univariate analyses, Kaplan-Meier methods, and log-rank tests, the prognostic value of various clinical predictors were assessed. Noncollinear predictors with P < .05 in univariate analyses were included in the final Cox proportional hazards model. RESULTS: The overall median survival was 7.7 months (range: 3 days-35.6 months); breast cancer had the longest median survival (12.1 months). Ten patients (7%), whose primary cancer was lung (3), kidney (3), sarcoma (2), prostate (1), and breast (1), died within 30 days postoperatively, and 88 had died at 12 months (62%). Univariate analyses yielded 8 significant predictors for survival: the growth of primary tumor (Tomita grade 1 vs grade 2 and 3), body mass index, sex, preoperative SF-36 physical component, EQ-5D, and Oswestry Disability Index (ODI) scores, as well as the presence of either visceral or extraspinal bony metastasis. The multiple regression analysis revealed that the Tomita grade (grade 1 vs grade 2 and 3; HR 2.81, P = .0007), the absence of visceral metastasis (HR 2.01; P = .0044), and higher score on SF-36 physical component (HR 0.945, P < .0001) were independent predictors for longer survival regardless of the selection method used (backward, forward, or stepwise). CONCLUSION: Slow-growing tumor (Tomita grade 1), absence of visceral metastasis, and lower degree of preoperative physical disability, as reflected by a higher score on the SF-36 physical component questionnaire, are good prognostic factors for survival in selected patients who underwent surgical treatment for a focal symptomatic MESCC lesion.